Peran Pekerja Sosial dalam Memberikan Pelayanan Sosial pada Lanjut Usia - Aris Hilmawan; Almisar Hamid (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The aging population will be a problem if the elderly have problems. The increasing number of problems elderly people confront may turn them into persons who need help to maintain their standard of living. Government-run institutions include the Tresna Werdha Social Service Center (BPSTW), where social workers play a crucial role in the delivery of social services. Social facilities for the elderly frequently face challenges with their residents' mobility, emotional and physical health, need for caregivers for daily activities, trouble adjusting, and lack of social interaction. Because it explains the role that social workers play in assisting the elderly, researchers are interested in studying